The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2197/ipsjjip.25.100
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Error Correction Using Classification of Transitions between Sequential Reading Segments

Abstract: Abstract:In eye-tracking-based reading behavior research, gaze sampling errors often negatively affect gaze-to-word mapping. In this paper, we propose a method for more accurate mapping by first taking adjacent horizontally progressive fixations as segments, and then classifying the segments into six classes using a random forest classifier. The segments are then reconstructed based on the classification, and are associated with a document line using a dynamic programming algorithm. The combination of segment-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…FixAlign, an R package developed by Cohen (2013), is currently the most well-established method in the experimental psychology community, although other methods have recently been proposed by Schroeder (2019) and Špakov et al (2019). In addition, there is a disparate body of work from several subfields of computer science, such as biometrics (Abdulin & Komogortsev, 2015), educational technology (Hyrskykari, 2006), and user-interface design (Beymer & Russell, 2005), in which various ad-hoc algorithms have been reported (see also Carl, 2013;Lima Sanches et al, 2015;Lohmeier, 2015;Martinez-Gomez et al, 2012;Mishra et al, 2012;Nüssli, 2011;Palmer & Sharif, 2016;Sibert et al, 2000;Yamaya et al, 2017).…”
Section: Figurementioning
confidence: 99%
“…FixAlign, an R package developed by Cohen (2013), is currently the most well-established method in the experimental psychology community, although other methods have recently been proposed by Schroeder (2019) and Špakov et al (2019). In addition, there is a disparate body of work from several subfields of computer science, such as biometrics (Abdulin & Komogortsev, 2015), educational technology (Hyrskykari, 2006), and user-interface design (Beymer & Russell, 2005), in which various ad-hoc algorithms have been reported (see also Carl, 2013;Lima Sanches et al, 2015;Lohmeier, 2015;Martinez-Gomez et al, 2012;Mishra et al, 2012;Nüssli, 2011;Palmer & Sharif, 2016;Sibert et al, 2000;Yamaya et al, 2017).…”
Section: Figurementioning
confidence: 99%
“…The compare algorithm is directly based on the method reported by Lima Sanches et al (2015) and is very similar to the more complex methods described by Yamaya et al (2017). The fixation sequence is first segmented into "gaze lines" by identifying the return sweeps-long saccades that move the eye from the end of one line to the start of the next.…”
Section: Comparementioning
confidence: 99%
“…Lima Sanches et al (2015) considered three measures of similarity and found dynamic time warping (DTW; Sakoe & Chiba, 1978;Vintsyuk, 1968) to be the best method (we discuss DTW in more detail later in this section). Similarly, Yamaya et al (2017) use the closely related Needleman-Wunsch algorithm (Needleman & Wunsch, 1970).…”
Section: Comparementioning
confidence: 99%
See 2 more Smart Citations